OPEN REGIONAL DATA AND THE USE OF AI - Radmila Velnerová; Petra Poulová (Trendy v podnikání)
This paper focuses on the topic of open data in public administration, specifically in a higher territorial self-government unit such as the Hradec Králové Region. It also describes the cooperation of the Hradec Králové Region as a public administration entity with the University of Hradec Králové in the field of research activities for open data and practical use through the application of artificial intelligence. The result of this cooperation was awarded the highest possible recognition by the expert community by winning the IT Project of the Year 2023 Award. The paper describes the process of cataloguing open data at the higher self-government units. Open data is centrally stored in a local open data catalogue according to the recommended rules of open formal standards. The local open data catalogue of this unit is part of the data portal of the region, which is a central information point for the public. Open data sets must be registered in the National Open Data Catalogue. One of the practical uses of open data is to implement applications for the public, as has been done with a research application using AI. An added bonus with this application is the practical use of AI for users. The design of the app was implemented during a hackathon by students of the University of Hradec Králové. Also, the quality of the open data of the Hradec Králové Region, over which this application is implemented, has been awarded the highest prizes by the expert community not only in the Czech Republic but also in Europe. The project of the Data Portal of the Hradec Králové Region was placed by the Organization for Economic Co-operation and Development (OECD) in the international catalogue of case studies of the Observatory of Public Sector Innovation (OPSI).